The impact of research education on student nurse attitude, skill and uptake of evidence‐based practice: a descriptive longitudinal survey. Issue 1 (January 2016) - Leach, Matthew J; Hofmeyer, Anne; Bobridge, Amanda
Abstract : Aims and Objectives: To measure the impact of an undergraduate research education program on the attitude, skill and uptake of evidence‐based practice among undergraduate student nurses. Background: The contribution of evidence‐based practice to clinical decision‐making, quality of care and patient outcomes is well‐documented. One approach to improving evidence‐based practice uptake in clinical practice is through the provision of undergraduate research education; notwithstanding, the impact of research training on nursing practice is poorly established. Design: Descriptive longitudinal survey. Methods: Three hundred and fifty four third‐year nursing students enrolled in a Bachelor of Nursing program of a large Australian University were invited. Pre‐ (Phase 1) and post‐completion (Phase 2) of a 16‐week research education program, participants were asked to complete the Evidence‐Based Practice Attitude and Utilization Survey; an 82‐item online questionnaire measuring attitudes, skills and use of evidence‐based practice, and barriers and facilitators of evidence‐based practice uptake. Results: The survey was completed by 84 (24%) participants in Phase 1 and 33 (39% of Phase 1) participants in Phase 2. Program exposure resulted in a significant improvement in median skill and use subscores, but not median attitude subscore. Participants perceived inadequate skills in the interpretation, appraisal and application of research findings to clinical practice as being less of a barrier to evidence‐based practice uptake posteducation, and access to online critical appraisal tools as being significantly more useful in facilitating evidence‐based practice uptake posteducation. Conclusions: The findings suggest that undergraduate research education may have a significant effect on nursing students' research skills and use of evidence‐based practice, and minimise barriers to evidence‐based practice uptake posteducation. Relevance to clinical practice: Undergraduate research education may play an important role in improving student nurse uptake of evidence‐based practice; whether these changes can be sustained when transitioning from student nurse to registered nurse is a question for further research.